Interventions to delay institutionalization of frail older persons: design of a longitudinal study in the home care setting - De Almeida Mello Johanna; Van Durme Therese; Macq Jean; Declercq Anja (BMC, 2012)
Abstract Background Older people usually prefer staying at home rather than going into residential care. The Belgian National Institute for Health and Disability Insurance wishes to invest in home care by financing innovative projects that effectively help older people to stay at home longer. In this study protocol we describe the evaluation of 34 home care projects. These projects are clustered according to the type of their main intervention such as case management, night care, occupational therapy at home and psychological/psychosocial support. The main goal of this study is to identify which types of projects have the most effect in delaying institutionalization of frail older persons. Methods/design This is a longitudinal intervention study based on a quasi-experimental design. Researchers use three comparison strategies to evaluate intervention - comparison among different types of projects, comparisons between older persons in the projects and older persons not benefiting from a project but who are still at home and between older persons in the projects and older persons who are already institutionalized. Projects are asked to include clients who are frail and at risk of institutionalization. In the study we use internationally validated instruments such as the interRAI Home Care instrument, the WHO-QOL-8 and the Zarit Burden Interview-12. These instruments are filled out at baseline, at exit from the project and 6 months after baseline. Additionally, caregivers have to do a follow-up every 6 months until exit from the project. Criteria to exit the cohort will be institutionalization longer than 3 months and death. The main analysis in the study consists of the calculation of incidence rates, cumulative incidence rates and hazard rates of definitive institutionalization through survival analyses for each type of project. Discussion This research will provide knowledge on the functional status of frail older persons who are still living at home. This is important information to identify determinants of risk for institutionalization. The identification of effective home care projects in delaying institutionalization will be useful to inform and empower home care providers, policy and related decision makers to manage and improve home care services.